Pyramiding and evaluation of both a foreign Bacillus thuringiensis and a Lysine-rich protein gene in the elite indica rice 9311 - Liu, Xin (Breeding science, 2016)
Gene pyramiding is an efficient approach for the genetic improvement of multiple agronomic traits simultaneously. In this study, we pyramided two foreign genes, cry1Ac driven by the rice Actin I promoter, and lysine-rich protein (LRP), driven by the endosperm-specific GLUTELIN1 (GT1) promoter, into the elite indica cultivar 9311. These two genes were chosen in an attempt to enhance insect-resistance and Lysine (Lys) content. In the pyramided line, the foreign gene cry1Ac was efficiently expressed in the leaves and stems, and exhibited highly efficient resistance to striped stem borer (SSB, Chilo suppressalis Walker) in the laboratory and rice leaf folder (RLF, Cnaphalocrocis medinalis Guenee) in the field. Furthermore, the LRP gene was highly expressed in the endosperm and produced a remarkable increase of Lys content in the seeds of the pyramided line. The data from field trials demonstrated that most of the agronomic traits including yield were well maintained in the pyramided line compared to the parental control. These results strongly suggest that the foreign cry1Ac and LRP genes have remarkable application potential in rice, and the resultant pyramided line serves as an ideal bridge material for the improvement of insect-resistance and high Lys rice in the future